Comparative analysis of single-pulse and two-pulse echo signals in cobalt micropowders and nanowires - Gavasheli, T.; Mamniashvili, G.; Gegechkori, T.; Donadze, G. (Edelweiss Applied Science and Technology, 2025)
This study compares the behavior of two-pulse and single-pulse echo signals in cobalt micropowders and nanowires. In the first instance, the analysis focused on the influence of an additional magnetic video pulse on the echo signals in cobalt micropowders. The findings confirm the edge mechanism responsible for single-pulse echo formation in cobalt micropowders, where the fronts of the radio-frequency pulse act analogously to the radio-frequency pulses in the two-pulse Hahn echo technique. In the second instance, the radiofrequency resonant magnetometry method evaluated the coercive force of cobalt nanowires embedded in a polymer matrix and polarized by a magnetic field. The two-pulse and single-pulse echo signals were also examined during the magnetization and remagnetization of cobalt nanowires in this sample. The results also align with the conclusion that the edge mechanism underpins single-pulse echo signal formation in this context. Understanding the SPE formation mechanism is crucial for exploring phenomena such as multiple TPE signals, cumulative echoes, and the use of magnets as spin processors.